Pre-marital Sex: Personal Choice or Moral Bound - Neupane , Shreeprasad (New Journey, 2023)
The recent news and opinions regarding the protest against violence and crimes meted out to women in our society. Women are being victimized by their husbands, lovers, mother/daughters-in-law and by the society as a whole. A sheer number of young girls and women are being raped, tortured and even murdered. Sex related issues are privileged in our society. The examples of violence indicate that over restriction on pre- marital sex seems to have enabled the youths to involve in sexual violence because of their curiosity on it. On the other hand, there are social ethics that create taboos on such activities. One cannot indict any single aspect of the society like youths, parents, guardians, educational factors and others as the causative agent of the violence. Because of the changing attitudes and beliefs, people have both the concepts of freedom as well as morality. Therefore, the issue of ‘pre-marital sex’ is a debatable domain prevalent in the society. The main aspect of this research article is to analyse the concept of some strong feminists regarding the topic related issue and also to make such social issues familiar among the readers and to check the possible violence and crimes in the society.